Machine learning and deep learning methods for exchange-traded fund trading - Jeremia, Alexander (Nanyang Technological University, 2023)
Machine Learning and Deep Learning has been growing in the popularity in many fields in the past few years especially in the field of Exchange Traded Funds (ETF) due to its ability to analyse large amount of data and detect patterns that might not be oblivious to traders. Additionally, these methods can process and analyse vast amounts of data in real-time, helping traders to make informed decisions, react quickly to changes in the market, and reduce the risk of losses. Due to the interest in the field, many have done research on the performance of different type of Machine Learning models.